Performance evaluation of a small scale gravity powered DC generator - Tagulao, Troy Cedric S. (Animo Repository, 2018)
In this study a small-scale gravitational device was design, fabricated and test. A small 5V DC generator was attached to a gear system that functions as a speed raiser with a gear ratio of 94.6224:1. The apparatus was operated with three electrical configuration system of electrical load, no load, 100 ohms, and 500 ohms with varying weight values from 250 to 2000 grams. The motivation of this study is to evaluate the performance parameters of the gravity-driven system specifically to the load applied, the output power, the current induced and analyze the effect of this various factors to the performance, efficiency and torque output of the system. In order to address the growing needs for sustainable energy solutions, a gravitational potential energy device that harness energy from a falling mass might provide an alternative solution as an alternative renewable energy source.